(untitled) (International Journal of Engineering and Computer Science, 2013)
As the number of Internet users is growing rapidly worldwide, Internet traffic data also increases. To analyze this traffic, multiple tools are available. But they do not perform well when the traffic data size increases. This traffic measurement and analysis is used to observe network usage behavior and perform different types of analysis. As the data grows it is necessary to increase the necessary infrastructure to process it. The Distributed File System can be used for this purpose, but it has certain limitations such as scalability, availability, and fault-tolerance. Hadoop is an open source distributed computing platform having MapReduce for distributed processing and HDFS to store huge amount of data. This study presents a Hadoop-based traffic monitoring system that performs a multiple types of analysis on huge amount of Internet traffic in a scalable manner.